Acrylic resin coating and preparation method thereof

By adding functional fillers to the aqueous acrylic resin coating, the zinc-titanium hydrotalc is synthesized by hydrothermal method and modifying the substrate, the toughness, impact resistance and photoaging of the coating are solved, and its corrosion resistance, flexibility and UV aging resistance are significantly improved.

CN119752262AInactive Publication Date: 2025-04-04GUANGDONG JIAYUAN NEW MATERIAL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411732014.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-04-04
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing aqueous acrylic resin coatings have problems such as poor toughness, poor impact resistance and prone to photoaging, resulting in a decline in the mechanical properties and appearance quality of the material.

Method used

By adding functional fillers to the acrylic resin coating, zinc-titanium hydrotalcitetrachloride, zinc nitrate and urea were used to synthesize a layered structure of zinc-titanium hydrotalcitetraligy by hydrothermal method, and the matrix was modified by γ-aminopropyltriethoxysilane, and intermediates were introduced to enhance UV absorption performance.

Benefits of technology

It significantly improves the corrosion resistance, flexibility and UV aging resistance of the paint, and extends the mechanical properties and appearance quality of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses an acrylic resin coating and a preparation method thereof, and belongs to the technical field of acrylic coatings, the acrylic resin coating comprises the following raw materials by weight: 50-80 parts of butyl acrylate, 30-50 parts of acrylic acid, 20-30 parts of methyl methacrylate, 10-15 parts of an emulsifier, 5-12 parts of a functional filler, 1-3 parts of an initiator, and 200-250 parts of deionized water; butyl acrylate, acrylic acid and methyl methacrylate are used as monomers, the coating is endowed with excellent performance by adding a functional filler, the functional filler is zinc-titanium hydrotalcite with a layered structure, a matrix can be endowed with ultraviolet absorption performance by introducing titanium, and the special layered structure can endow the coating with good corrosion resistance. By introducing an intermediate, the intermediate is grafted on the surface of the matrix, and the intermediate is used as a benzophenone derivative, has excellent ultraviolet absorption performance, and can cooperate with the titanium element on the matrix to endow the coating with excellent ultraviolet aging resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of acrylic paint, and in particular to an acrylic resin paint and a preparation method thereof. Background Art

[0002] Acrylic resin coating is a thermoplastic or thermosetting resin coating made of acrylic resin obtained by copolymerizing (meth)acrylate and styrene with other acrylic esters. Compared with traditional solvent-based coatings, water-based acrylic resin coatings have the advantages of low price, safe use, saving resources and energy, and reducing environmental pollution and public hazards. The varnish made from water-soluble acrylic resin has the characteristics of being non-toxic and odorless, acid and alkali resistant, high gloss, good adhesion, no fading and chemical resistance. It is a green and environmentally friendly product with low volatile organic compounds (VOC) and is widely used in the field of architectural coatings. However, the current water-based acrylic resin has problems such as poor toughness and poor impact resistance. In addition, acrylic resin is prone to photoaging when exposed to sunlight for a long time, resulting in a decrease in the mechanical properties and appearance quality of the material. Summary of the invention

[0003] In order to solve the above technical problems, the present invention provides an acrylic resin coating and a preparation method thereof.

[0004] The purpose of the present invention can be achieved by the following technical solutions: An acrylic resin coating comprises the following raw materials in parts by weight: 50-80 parts of butyl acrylate, 30-50 parts of acrylic acid, 20-30 parts of methyl methacrylate, 10-15 parts of emulsifier, 5-12 parts of functional filler, 1-3 parts of initiator, and 200-250 parts of deionized water; The functional filler is prepared by the following method: Step S1, adding 20% ​​by mass titanium tetrachloride solution, zinc nitrate and urea to deionized water in sequence, heating to 110-120° C. in an oil bath, keeping warm and reacting for 24 hours, cooling to room temperature after the reaction, washing with deionized water and anhydrous ethanol three times respectively, and then drying at 65° C. to obtain a matrix; In step S1, titanium tetrachloride is used as a titanium source, zinc nitrate is used as a zinc source, and urea is used as a precipitant. The matrix is ​​synthesized by a hydrothermal method. The matrix is ​​a zinc-titanium hydrotalcite with a layered structure. The introduction of titanium element can give the matrix ultraviolet absorption properties, and the special layered structure can give the coating good corrosion resistance.

[0005] Step S2, adding the prepared substrate into a 10% by mass ethanol aqueous solution, adding γ-aminopropyltriethoxysilane, stirring at a uniform speed and reacting for 4-6 hours to prepare a modified substrate; In step S2, the substrate is modified by using a silane coupling agent, γ-aminopropyltriethoxysilane, to introduce amino groups on the surface of the substrate.

[0006] Step S3, adding 2,4-dihydroxybenzophenone to toluene, stirring at a uniform speed and adding epichlorohydrin and tetrabutylammonium bromide, heating to 60-65° C., adding a 45% by mass aqueous sodium hydroxide solution, continuing stirring and reflux reaction for 3 hours, heating to 80° C. after the reaction is completed, adding a 45% by mass aqueous sodium hydroxide solution, and continuing reflux reaction for 3 hours to obtain an intermediate; In step S3, under the action of tetrabutylammonium bromide as a catalyst, 2,4-dihydroxybenzophenone and epichlorohydrin undergo a ring-opening reaction, and then re-cyclize under alkaline conditions to prepare an intermediate, and an epoxy group is introduced into the structure of 2,4-dihydroxybenzophenone.

[0007] Step S4, adding the modified matrix into N,N-dimethylformamide, adding the intermediate, heating to 45-55° C., stirring at a constant speed and reacting for 2-4 hours to obtain a functional filler.

[0008] In step S4, the amino group on the modified substrate reacts with the epoxy group on the intermediate, and then the intermediate is grafted onto the surface of the substrate. The intermediate itself, as a benzophenone derivative, has excellent ultraviolet absorption performance and can cooperate with the titanium element on the substrate to give the coating excellent ultraviolet aging resistance.

[0009] Furthermore, the emulsifier is sodium dodecyl sulfate or sodium dodecylbenzene sulfonate.

[0010] Furthermore, the initiator is azobisisobutyronitrile.

[0011] Furthermore, in step S1, the dosage ratio of titanium tetrachloride solution, zinc nitrate, urea and deionized water is controlled to be 0.25-0.3 mL: 2.35-2.40 g: 2-3 g: 50 mL.

[0012] Furthermore, in step S2, the weight ratio of the substrate, γ-aminopropyltriethoxysilane and ethanol aqueous solution is controlled to be 1-2:0.2-0.25:10-15.

[0013] Furthermore, in step S3, the total volume ratio of 2,4-dihydroxybenzophenone, epichlorohydrin, tetrabutylammonium bromide, sodium hydroxide aqueous solution and toluene is controlled to be 2.12-2.16 g:4.2-4.5 mL:0.02-0.05 g:3 mL:12 mL, and the volume ratio of the sodium hydroxide aqueous solution added twice is 1:2.

[0014] Furthermore, in step S4, the weight ratio of the modified substrate, the intermediate and N,N-dimethylformamide is controlled to be 1-2:0.3-0.5:10.

[0015] A method for preparing an acrylic resin coating comprises the following steps: Add butyl acrylate, acrylic acid and methyl methacrylate into deionized water, add emulsifier, stir at a constant speed for 10-15 minutes, add initiator and functional filler, continue stirring for 30 minutes to prepare acrylic resin coating.

[0016] Beneficial effects of the present invention: The invention prepares an acrylic resin coating, wherein butyl acrylate, acrylic acid and methyl methacrylate are used as monomers, and excellent performance is given to the coating by adding a functional filler. In the preparation process of the functional filler, titanium tetrachloride is used as a titanium source, zinc nitrate is used as a zinc source, and urea is used as a precipitant. A matrix is ​​synthesized by a hydrothermal method, and the matrix is ​​a zinc-titanium hydrotalcite with a layered structure. The introduction of titanium element can give the matrix ultraviolet absorption performance, and the special layered structure can give the coating good corrosion resistance. In addition, an intermediate is introduced and grafted on the surface of the substrate. The intermediate itself is a benzophenone derivative and has excellent ultraviolet absorption performance, and can cooperate with the titanium element on the substrate to give the coating excellent ultraviolet aging resistance. DETAILED DESCRIPTION

[0017] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1

[0018] An acrylic resin coating comprises the following raw materials in parts by weight: 50 parts of butyl acrylate, 30 parts of acrylic acid, 20 parts of methyl methacrylate, 10 parts of emulsifier, 5 parts of functional filler, 1 part of initiator, and 200 parts of deionized water; The preparation method of acrylic resin coating comprises the following steps: Butyl acrylate, acrylic acid and methyl methacrylate were added into deionized water, and an emulsifier was added, and the mixture was stirred at a constant speed for 10 minutes. An initiator and a functional filler were added, and the mixture was stirred for 30 minutes to obtain an acrylic resin coating.

[0019] The functional filler is prepared by the following method: Step S1, adding a 20% mass fraction titanium tetrachloride solution, zinc nitrate and urea to deionized water in sequence, heating to 110°C in an oil bath, keeping warm and reacting for 24 hours, cooling to room temperature after the reaction, washing with deionized water and anhydrous ethanol three times respectively, and then drying at 65°C to obtain a matrix, wherein the amount ratio of titanium tetrachloride solution, zinc nitrate, urea and deionized water is controlled to be 0.25mL:2.35g:2g:50mL; Step S2, adding the prepared substrate to a 10% by mass ethanol aqueous solution, adding γ-aminopropyltriethoxysilane, stirring at a uniform speed and reacting for 4 hours to obtain a modified substrate, and controlling the weight ratio of the substrate, γ-aminopropyltriethoxysilane and the ethanol aqueous solution to be 1:0.2:10; Step S3, adding 2,4-dihydroxybenzophenone to toluene, stirring at a uniform speed and adding epichlorohydrin and tetrabutylammonium bromide, heating to 60°C, adding a 45% by mass sodium hydroxide aqueous solution, continuing stirring and reflux reaction for 3 hours, heating to 80°C after the reaction, adding a 45% by mass sodium hydroxide aqueous solution, and continuing reflux reaction for 3 hours to obtain an intermediate, controlling the total volume of 2,4-dihydroxybenzophenone, epichlorohydrin, tetrabutylammonium bromide, sodium hydroxide aqueous solution and toluene to be 2.12g:4.2mL:0.02g:3mL:12mL, and the volume ratio of the sodium hydroxide aqueous solution added twice is 1:2; Step S4, adding the modified matrix to N, N-dimethylformamide, adding the intermediate, heating to 45°C, stirring at a constant speed and reacting for 2 hours to obtain a functional filler, and controlling the weight ratio of the modified matrix, the intermediate and N, N-dimethylformamide to be 1:0.3:10.

[0020] The emulsifier is sodium lauryl sulfate.

[0021] The initiator is azobisisobutyronitrile.

[0022] Example 2: An acrylic resin coating comprises the following raw materials in parts by weight: 60 parts of butyl acrylate, 40 parts of acrylic acid, 25 parts of methyl methacrylate, 12 parts of emulsifier, 8 parts of functional filler, 2 parts of initiator, and 220 parts of deionized water; The preparation method of acrylic resin coating comprises the following steps: Butyl acrylate, acrylic acid and methyl methacrylate were added into deionized water, and emulsifier was added, and stirred at a constant speed for 12 minutes. Initiator and functional filler were added, and stirring was continued for 30 minutes to prepare acrylic resin coating.

[0023] The functional filler is prepared by the following method: Step S1, adding a 20% mass fraction titanium tetrachloride solution, zinc nitrate and urea to deionized water in sequence, heating to 110°C in an oil bath, keeping warm and reacting for 24 hours, cooling to room temperature after the reaction, washing with deionized water and anhydrous ethanol three times respectively, and then drying at 65°C to obtain a matrix, wherein the amount ratio of titanium tetrachloride solution, zinc nitrate, urea and deionized water is controlled to be 0.26mL:2.38g:2.5g:50mL; Step S2, adding the prepared substrate to a 10% by mass ethanol aqueous solution, adding γ-aminopropyltriethoxysilane, stirring at a uniform speed and reacting for 5 hours to obtain a modified substrate, and controlling the weight ratio of the substrate, γ-aminopropyltriethoxysilane and the ethanol aqueous solution to be 1.5:0.22:10; Step S3, adding 2,4-dihydroxybenzophenone to toluene, stirring at a uniform speed and adding epichlorohydrin and tetrabutylammonium bromide, heating to 60°C, adding a 45% by mass sodium hydroxide aqueous solution, continuing stirring and reflux reaction for 3 hours, heating to 80°C after the reaction, adding a 45% by mass sodium hydroxide aqueous solution, and continuing reflux reaction for 3 hours to obtain an intermediate, controlling the total volume of 2,4-dihydroxybenzophenone, epichlorohydrin, tetrabutylammonium bromide, sodium hydroxide aqueous solution and toluene to be 2.14g:4.4mL:0.03g:3mL:12mL, and the volume ratio of the sodium hydroxide aqueous solution added twice is 1:2; Step S4, adding the modified matrix to N, N-dimethylformamide, adding the intermediate, heating to 55°C, stirring at a constant speed and reacting for 4 hours to obtain a functional filler, and controlling the weight ratio of the modified matrix, the intermediate and N, N-dimethylformamide to be 1.5:0.4:10.

[0024] The emulsifier is sodium lauryl sulfate.

[0025] The initiator is azobisisobutyronitrile.

[0026] Example 3: An acrylic resin coating comprises the following raw materials in parts by weight: 70 parts of butyl acrylate, 45 parts of acrylic acid, 25 parts of methyl methacrylate, 14 parts of emulsifier, 10 parts of functional filler, 2 parts of initiator, and 250 parts of deionized water; The preparation method of acrylic resin coating comprises the following steps: Butyl acrylate, acrylic acid and methyl methacrylate were added into deionized water, and emulsifier was added, and stirred at a constant speed for 15 minutes. Initiator and functional filler were added, and stirring was continued for 30 minutes to prepare acrylic resin coating.

[0027] The functional filler is prepared by the following method: Step S1, adding a 20% mass fraction titanium tetrachloride solution, zinc nitrate and urea to deionized water in sequence, heating to 120°C in an oil bath, keeping warm and reacting for 24 hours, cooling to room temperature after the reaction, washing with deionized water and anhydrous ethanol three times respectively, and then drying at 65°C to obtain a matrix, wherein the amount ratio of titanium tetrachloride solution, zinc nitrate, urea and deionized water is controlled to be 0.3mL:2.40g:2.5g:50mL; Step S2, adding the prepared substrate to a 10% by mass ethanol aqueous solution, adding γ-aminopropyltriethoxysilane, stirring at a uniform speed and reacting for 6 hours to obtain a modified substrate, and controlling the weight ratio of the substrate, γ-aminopropyltriethoxysilane and the ethanol aqueous solution to be 1.8:0.4:14; Step S3, adding 2,4-dihydroxybenzophenone to toluene, stirring at a uniform speed and adding epichlorohydrin and tetrabutylammonium bromide, heating to 65°C, adding a 45% by mass sodium hydroxide aqueous solution, continuing stirring and reflux reaction for 3 hours, heating to 80°C after the reaction, adding a 45% by mass sodium hydroxide aqueous solution, and continuing reflux reaction for 3 hours to obtain an intermediate, controlling the total volume of 2,4-dihydroxybenzophenone, epichlorohydrin, tetrabutylammonium bromide, sodium hydroxide aqueous solution and toluene to be 2.14 g: 4.4 mL: 0.04 g: 3 mL: 12 mL, and the volume ratio of the sodium hydroxide aqueous solution added twice is 1: 2; Step S4, adding the modified matrix to N,N-dimethylformamide, adding the intermediate, heating to 55°C, stirring at a constant speed and reacting for 4 hours to obtain a functional filler, and controlling the weight ratio of the modified matrix, the intermediate and N,N-dimethylformamide to be 1.8:0.5:10.

[0028] The emulsifier is sodium dodecylbenzene sulfonate.

[0029] The initiator is azobisisobutyronitrile.

[0030] Example 4: An acrylic resin coating comprises the following raw materials in parts by weight: 80 parts of butyl acrylate, 50 parts of acrylic acid, 30 parts of methyl methacrylate, 15 parts of emulsifier, 12 parts of functional filler, 3 parts of initiator, and 250 parts of deionized water; The preparation method of acrylic resin coating comprises the following steps: Butyl acrylate, acrylic acid and methyl methacrylate were added into deionized water, and emulsifier was added, and stirred at a constant speed for 15 minutes. Initiator and functional filler were added, and stirring was continued for 30 minutes to prepare acrylic resin coating.

[0031] The functional filler is prepared by the following method: Step S1, adding a 20% mass fraction titanium tetrachloride solution, zinc nitrate and urea to deionized water in sequence, heating to 120°C in an oil bath, keeping warm and reacting for 24 hours, cooling to room temperature after the reaction, washing with deionized water and anhydrous ethanol three times respectively, and then drying at 65°C to obtain a matrix, wherein the amount ratio of titanium tetrachloride solution, zinc nitrate, urea and deionized water is controlled to be 0.3mL:2.40g:3g:50mL; Step S2, adding the prepared substrate to a 10% by mass ethanol aqueous solution, adding γ-aminopropyltriethoxysilane, stirring at a uniform speed and reacting for 6 hours to obtain a modified substrate, and controlling the weight ratio of the substrate, γ-aminopropyltriethoxysilane and the ethanol aqueous solution to be 2:0.25:15; Step S3, adding 2,4-dihydroxybenzophenone to toluene, stirring at a uniform speed and adding epichlorohydrin and tetrabutylammonium bromide, heating to 65°C, adding a 45% by mass sodium hydroxide aqueous solution, continuing stirring and reflux reaction for 3 hours, heating to 80°C after the reaction, adding a 45% by mass sodium hydroxide aqueous solution, and continuing reflux reaction for 3 hours to obtain an intermediate, controlling the total volume of 2,4-dihydroxybenzophenone, epichlorohydrin, tetrabutylammonium bromide, sodium hydroxide aqueous solution and toluene to be 2.16 g: 4.5 mL: 0.05 g: 3 mL: 12 mL, and the volume ratio of the sodium hydroxide aqueous solution added twice is 1: 2; Step S4, adding the modified matrix to N, N-dimethylformamide, adding the intermediate, heating to 55°C, stirring at a constant speed and reacting for 4 hours to obtain a functional filler, and controlling the weight ratio of the modified matrix, the intermediate and N, N-dimethylformamide to be 2:0.5:10.

[0032] The emulsifier is sodium dodecylbenzene sulfonate.

[0033] The initiator is azobisisobutyronitrile.

[0034] Comparative Example 1 Compared with Example 1, this comparative example uses the matrix prepared in step S1 as the functional filler, and the rest is the same as Example 1.

[0035] Comparative Example 2 Compared with Example 1, this comparative example uses a commercially available benzophenone ultraviolet absorber to replace the functional filler, and the preparation method is as follows: An acrylic resin coating comprises the following raw materials in parts by weight: 50 parts of butyl acrylate, 30 parts of acrylic acid, 20 parts of methyl methacrylate, 10 parts of emulsifier, 5 parts of benzophenone ultraviolet absorber, 1 part of initiator, and 200 parts of deionized water; The preparation method of acrylic resin coating comprises the following steps: Butyl acrylate, acrylic acid and methyl methacrylate were added into deionized water, and an emulsifier was added, and the mixture was stirred at a constant speed for 10 minutes. An initiator and a benzophenone type UV absorber were added, and the mixture was stirred for 30 minutes to obtain an acrylic resin coating.

[0036] The rest is the same as in Example 1.

[0037] The properties of the coatings prepared in Examples 1-4 and Comparative Examples 1-2 were tested, and the results are shown in Table 1 below: The flexibility of the coating film is measured using the national standard GB / T 1731-1993 "Determination of paint film flexibility"; The pencil hardness of the coating is determined to be 6B-6H using the national standard GB / T 6739-1996 "Coating Hardness Pencil Determination Method"; The national standard GB / T 1763-79 "Determination of chemical resistance of paint film" is used to determine the acid and alkali resistance of the coating film;

[0038] It can be seen from Table 1 above that the coatings prepared in Examples 1-4 of the present invention have excellent corrosion resistance and flexibility.

[0039] The obtained coating was cured to form a cured film, and the mechanical properties were tested according to the method of GB / T 1040.1-2018. Then, the film was aged for 120 h in a UV accelerated aging tester with a light source wavelength of 340 nm and an irradiance of 0.78 W / (m 2 *nm), relative humidity 60%, and tensile properties test was performed again. The results are shown in Table 2 below:

[0040] It can be seen from Table 2 above that the coating prepared in the embodiment of the present invention has excellent mechanical properties and even better resistance to ultraviolet aging.

[0041] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. An acrylic resin coating, characterized in that: The invention comprises the following raw materials in parts by weight: 50-80 parts of butyl acrylate, 30-50 parts of acrylic acid, 20-30 parts of methyl methacrylate, 10-15 parts of emulsifier, 5-12 parts of functional filler, 1-3 parts of initiator, and 200-250 parts of deionized water; The functional filler is prepared by the following method: Step S1, adding 20% ​​by mass titanium tetrachloride solution, zinc nitrate and urea to deionized water in sequence, heating to 110-120° C. in an oil bath, keeping warm and reacting for 24 hours, cooling to room temperature after the reaction, washing with deionized water and anhydrous ethanol three times respectively, and then drying at 65° C. to obtain a matrix; Step S2, adding the prepared substrate into a 10% by mass ethanol aqueous solution, adding γ-aminopropyltriethoxysilane, stirring at a uniform speed and reacting for 4-6 hours to prepare a modified substrate; Step S3, adding 2,4-dihydroxybenzophenone to toluene, stirring at a uniform speed and adding epichlorohydrin and tetrabutylammonium bromide, heating to 60-65° C., adding a 45% by mass aqueous sodium hydroxide solution, continuing stirring and reflux reaction for 3 hours, heating to 80° C. after the reaction is completed, adding a 45% by mass aqueous sodium hydroxide solution, and continuing reflux reaction for 3 hours to obtain an intermediate; Step S4, adding the modified matrix into N,N-dimethylformamide, adding the intermediate, heating to 45-55° C., stirring at a constant speed and reacting for 2-4 hours to obtain a functional filler.

2. An acrylic resin coating according to claim 1, characterized in that: The emulsifier is sodium dodecyl sulfate or sodium dodecylbenzene sulfonate.

3. An acrylic resin coating according to claim 1, characterized in that: The initiator is azobisisobutyronitrile.

4. An acrylic resin coating according to claim 1, characterized in that: In step S1, the dosage ratio of titanium tetrachloride solution, zinc nitrate, urea and deionized water is controlled to be 0.25-0.3 mL: 2.35-2.40 g: 2-3 g: 50 mL.

5. An acrylic resin coating according to claim 1, characterized in that: In step S2, the weight ratio of the substrate, γ-aminopropyltriethoxysilane and ethanol aqueous solution is controlled to be 1-2:0.2-0.25:10-15.

6. An acrylic resin coating according to claim 1, characterized in that: In step S3, the total volume ratio of 2,4-dihydroxybenzophenone, epichlorohydrin, tetrabutylammonium bromide, sodium hydroxide aqueous solution and toluene is controlled to be 2.12-2.16 g:4.2-4.5 mL:0.02-0.05 g:3 mL:12 mL, and the volume ratio of the sodium hydroxide aqueous solution added twice is 1:

2.

7. An acrylic resin coating according to claim 1, characterized in that: In step S4, the weight ratio of the modified substrate, the intermediate and N,N-dimethylformamide is controlled to be 1-2:0.3-0.5:

10.

8. The method for preparing an acrylic resin coating according to claim 1, characterized in that: The steps include: Add butyl acrylate, acrylic acid and methyl methacrylate into deionized water, add emulsifier, stir at a constant speed for 10-15 minutes, add initiator and functional filler, continue stirring for 30 minutes to prepare acrylic resin coating.

Citation Information

Patent Citations

  • Novel lamina-like ultraviolet absorbing material and preparing method

    CN101024759A

  • Method for preparing polymer / houghite nano composite material

    CN101560271A

  • Preparation method of layered doubled hydroxide modified polyacrylate composite emulsion

    CN105801748A

  • Production method of super-hydrophobic anti-ultraviolet fabric

    CN108642869A

  • Preparation method of toughened weather-resistant EB curing coating

    CN115304993A